Membangun Karakter Keluarga Katolik (Kepada Umat Lingkungan) Stasi ST. Yosep Suka Maju, Paroki Tanjung Selamat Medan - Tri Sujarwadi (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
The rapid development of technology in the current era of globalization has had a negative impact on the moral development of teenagers. There needs to be an effort made by the adult community to shape the character of the younger generation so that they can recognize their potential. For this reason, as scholars who play a role in the world of education, by looking at the development of the character of the young generation in the current era of globalization, we, the service team, are encouraged to also make our contribution through socialization and training to children, especially ST Station children. Yosep Suka Maju, Tanjung Selamat Parish, Medan, with the activity theme "Building Catholic Family Character (To Community Community) Stasi St. Yosep Likes to Move Forward, Tanjung Selamat Parish, Medan." Apart from the presentation of Leadership and Free Association material, discussions and training were also provided using the Community Education method. We really hope that every material provided can provide good education for children in particular and also students who are involved in service activities.